The inverse link between genetic risk for schizophrenia and migraine through NMDA (N-methyl-D-aspartate) receptor activation via D-serine - Auwera, Sandra van der; Rietschel, Marcella (European neuropsychopharmacology, 2016)
Schizophrenia has a considerable genetic background. Epidemiological studies suggest an inverse clinical association between schizophrenia and migraine. However, it is unclear to what extent this inverse comorbidity can be explained by genetic mechanisms or by schizophrenia-related behavioral factors. For both disorders hypotheses of glutamate N-methyl-D-aspartate (NMDA) receptor dysfunction have been developed in the past. We hypothesized that both conditions share common genetic factors with inverse effects, primary in the glutamatergic system and genes involved in NMDA activation. Data from the population based Study of Health in Pomerania (N=3973) were used. Based on the results from the recent genome-wide association study for schizophrenia, we calculated polygenic scores (PRS) for subsets of SNPs with different p-value cutoffs and for biological sub-entities. These scores were tested for an association of distinct biological pathways with migraine. The PRS for schizophrenia was inversely associated with migraine in our sample. This association was exclusively based on the genome-wide hits and on single nucleotide polymorphisms near or within genes encoding proteins involved in glutamatergic neurotransmission. This association could be attributed to a single intronic variant rs4523957 in SRR encoding serine-racemase. Additional expression quantitative trait loci analyses of functional variants in SRR and gene-by-gene interaction analyses further supported the validity of this finding. SRR represents the rate limiting enzyme for the synthesis of D-serine, an important co-agonist of the NMDA receptor. According to our results, a decreased versus increased activation of NMDA receptors may play a role in the etiology of schizophrenia, as well as in migraine.
Gesehen am 08.02.2018